Determinación del contenido total de hongos de 12 especies vegetales cultivadas en Ecuador - Medina Caiminagua, Mariuxi Lissette (2015)
The use of medicinal plants is one of the oldest and most widespread medical therapies remote to prehistoric times , and now also used in the preparation son of herbal medicines with options to cure diseases